2010
DOI: 10.1590/s1516-31802010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Causes of discontinuity of blood donation among donors in Shiraz, Iran: cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: The adequacy of blood depends on blood donation rates and numbers of blood donors. To prepare adequate blood supplies, it is essential to investigate the barriers and factors that stop individuals from donating. This study aimed to identify the causes of lapsed donation at our center. DESIGN AND SETTING:Cross-sectional study of volunteer blood donors in Shiraz, Iran. The participants were recruited by letter and telephone, and were interviewed using a specially designed questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…11 Among firsttime donors, one of the most important reasons for not returning to donate is lack of qualification for donation. 12 An appraisal of blood donation in Iran showed that just 34.8% of Iranian blood donors who had been rejected in 1999 gave blood over the subsequent three years. 13 In the Iranian Blood Transfusion Organization (IBTO), Hb and/or hematocrit (Hct) assessments are used as a screening criterion for eligibility to donate blood.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among firsttime donors, one of the most important reasons for not returning to donate is lack of qualification for donation. 12 An appraisal of blood donation in Iran showed that just 34.8% of Iranian blood donors who had been rejected in 1999 gave blood over the subsequent three years. 13 In the Iranian Blood Transfusion Organization (IBTO), Hb and/or hematocrit (Hct) assessments are used as a screening criterion for eligibility to donate blood.…”
Section: Introductionmentioning
confidence: 99%
“…This is because women are disallowed from donating during pregnancy or breastfeeding periods, and thus quit donating permanently instead of resuming to donate later. Another possible reason accounting for lower donation rates among women include health concerns, such as iron-deficiency anaemia or low body weight (Boulware et al, 2002;Kasraian, 2010). It is therefore posited that males would exhibit higher likelihoods of being occasional or regular donors than females in the current study.…”
Section: Insights From the Literaturementioning
confidence: 80%
“…In other words, being married serves as a strong positive predictor of blood donation only among men, while the association is not as evident for women. Meanwhile, Kasraian (2010) and Shenga et al (2010) find no significant relationship between blood donation knowledge and marital status. Thus, the role of marital status on blood donation status will be further examined in the current study.…”
Section: Insights From the Literaturementioning
confidence: 85%
See 2 more Smart Citations